Investigation of the efficacy of low-frequency repetitive transcranial magnetic stimulation on upper-limb motor recovery in subacute ischemic stroke without cortical involvement: a protocol paper for a multi-center, double-blind randomized controlled trial - Cho, Hee-Mun; Cha, Seungwoo; Sohn, Min Kyun; Jee, Sungju; Chang, Won Kee; Kim, Won-Seok; Paik, Nam-Jong (Frontiers in Neurology, 2023)
Introduction The incidence of stroke is increasing steadily due to factors such as population aging. Approximately 80% of stroke survivors have motor disorders affecting their daily lives. Repetitive transcranial magnetic stimulation (rTMS) has been reported to maximize functional recovery after stroke along with exercise intervention in upper limb rehabilitation treatment. However, whether rTMS affects the recovery of upper limb function in patients with stroke remains unclear. Therefore, in this trial, we will investigate the efficacy of low-frequency rTMS in patients with subcortical and brainstem ischemic stroke. Methods This study has been designed as a multi-center, double-blind, randomized controlled trial to compare the efficacy of low-frequency rTMS over the contralesional M1 with sham stimulation. Overall, 88 participants will be allocated to the intervention or control group in a 1:1 ratio, with stratification according to their initial upper extremity Fugl-Meyer assessment (UE-FMA) score. The participants will receive either 30 min of real rTMS (intervention group) or sham rTMS (control group), followed by 30 min of occupational therapy for 10 consecutive workdays. All the participants will receive the same amount of rehabilitation therapy throughout the intervention period. Evaluations will be performed at baseline (T0), at the end of treatment (T1), and 4 weeks after the end of treatment (T2), including the box and block test (BBT), UE-FMA, Korean version of the Modified Barthel Index, and NIH Stroke Scale scores, Finger tapping test, Brunnstrom stage, modified Ashworth scale, and grip strength. The primary outcome will be the change in the BBT score between T0 and T2. Conclusion This study will provide evidence on the efficacy of low-frequency rTMS in motor function recovery of the upper limb in patients with subacute, subcortical, and brainstem ischemic stroke. Clinical trial registration ClinicalTrials.gov, identifier [NCT05535504].